Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.virusres.2020.198190
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory drugs and the renin-angiotensin-aldosterone system: Current knowledge and potential effects on early SARS-CoV-2 infection

Abstract: Highlights SARS-CoV-2 expresses viral S-protein that exploits ACE2 to gain host cell entry. The renin-angiotensin-aldosterone system influences SARS-CoV-2 pathogenicity. ACE2-mediated endothelial infection partially explains vascular pathologies in COVID-19. NSAIDs enhance viral replication and shedding in several known viruses. Corticosteroids mediate pathways that may aggravate early infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…In clinical studies of small cohorts of COVID-19 patients, treatment with NSAIDs was associated with either adverse clinical outcomes ( Jeong et al, 2020 ) or no effect on mortality rate ( Abu Esba et al, 2020 ; Chandan et al, 2020 ; Lund et al, 2020 ) or a modest beneficial effect on survival rates ( Bruce et al, 2020 ). The mechanisms of NSAID actions and their potential use in COVID-19 patients have recently been discussed ( Cabbab & Manalo, 2020 ; Micallef, Soeiro, & Jonville-Béra, 2020 ). The effects of steroids, NSAIDs, and pharmacologically related compounds on ACE2 activity and expression are summarized in Table 6 .…”
Section: Corticosteroids Non-steroid Anti-inflammatory Drugs and Acmentioning
confidence: 99%
“…In clinical studies of small cohorts of COVID-19 patients, treatment with NSAIDs was associated with either adverse clinical outcomes ( Jeong et al, 2020 ) or no effect on mortality rate ( Abu Esba et al, 2020 ; Chandan et al, 2020 ; Lund et al, 2020 ) or a modest beneficial effect on survival rates ( Bruce et al, 2020 ). The mechanisms of NSAID actions and their potential use in COVID-19 patients have recently been discussed ( Cabbab & Manalo, 2020 ; Micallef, Soeiro, & Jonville-Béra, 2020 ). The effects of steroids, NSAIDs, and pharmacologically related compounds on ACE2 activity and expression are summarized in Table 6 .…”
Section: Corticosteroids Non-steroid Anti-inflammatory Drugs and Acmentioning
confidence: 99%
“…SARS-CoV-2 enters respiratory epithelial cells via ACE2 interactions, causing receptor internalization and subsequent down-regulation (21). Reduced ACE2 levels, which have been shown to regulate RAS, could lead to RAS dysfunction, potentially enhancing inflammation and airway vascular permeability (22).…”
Section: Renin-angiotensin System (Ras) Dysfunctionmentioning
confidence: 99%
“…The World Health Organization (WHO) initially recommended that ibuprofen and other non-steroidal anti-inflammatory drugs (NSAIDs) should be avoided in the management of COVID-19 symptoms as there were anecdotal reports that NSAIDs such as ibuprofen could worsen effects of SARS-CoV-2 during the early phase of COVID-19[ 22 ]. WHO later withdrew their recommendation because of a lack of clinical evidence[ 22 ]. Indeed, Rinott and colleagues[ 23 ] reported that ibuprofen use was not associated with worse clinical outcomes when compared to paracetamol or no antipyretic use.…”
Section: Non-steroidal Anti-inflammatory Drugs and Paracetamolmentioning
confidence: 99%
“…22 WHO later withdrew their recommendation because of a lack of clinical evidence. 22 Indeed, Rinott and colleagues 23 reported that ibuprofen use was not associated with worse clinical outcomes when compared with paracetamol or no antipyretic use.…”
Section: Nsaids and Paracetamolmentioning
confidence: 99%